Modeling of haemostatic tourniquet based on the relationship with phsiological parameters - Skoba, Vladyslav (Запорізький державний медичний університет, 2021)
The purpose of the presented work is to determine the physical and technical characteristics of toкurniquet (device that is used in emergencies or extremity in order to limit or stop the flow of blood); comparative analysis of design features that affect the efficiency and safety of tourniquets; detection of the relationship between the mechanical moment of beam compression and pressure and physiological parameters and individual characteristics of patients.
Keywords: тези